The beginnings of the philosophy of difference in France - Kwietniewska, Małgorzata (Hybris, 2016)
The article presents a general characterisation of Maurice Merleau-Ponty’s thought, particularly pointing to an ambivalence in his views. According to the author, this ambivalence is created on purpose and leads the philosopher to initiate a French version of philosophy of difference. It turns out that though Merleau-Ponty declares appreciation towards Husserl’s phenomenology and Sartre’s existentialism, he is closer to classical German philosophy: Hegel and Heidegger.